Whitefly population dynamics in okra plantations - Leite, Germano Leão Demolin; Picanço, Marcelo; Jham, Gulab Newandram; Moreira, Márcio Dionízio (Pesquisa Agropecuaria Brasileira, 2005)
The control of whitefly Bemisia tabaci (Gennadius) biotype B (Hemiptera: Aleyrodidae) on okra (Abelmoschus esculentus L.) consists primarily in the use of insecticides, due to the lack of information on other mortality factors. The objective of this study was to evaluate the spatial and temporal population dynamics of the whitefly B. tabaci biotype B on two successive A. esculentus var. "Santa Cruz" plantations. Leaf chemical composition, leaf nitrogen and potassium contents, trichome density, canopy height, plant age, predators, parasitoids, total rainfall and median temperature were evaluated and their relationships with whitefly on okra were determined. Monthly number estimates of whitefly adults, nymphs (visual inspection) and eggs (magnifying lens) occurred on bottom, middle and apical parts of 30 plants/plantation (one leaf/plant). Plants senescence and natural enemies, mainly Encarsia sp., Chrysoperla spp. and Coccinellidae, were some of the factors that most contributed to whitefly reduction. The second okra plantation, 50 m apart from the first, was strongly attacked by whitefly, probably because of the insect migration from the first to the second plantation. No significant effects of the plant canopy on whitefly eggs and adults distribution were found. A higher number of whitefly nymphs was found on the medium part than on the bottom part.